MODEL PENGEMBANGAN KOMPETENSI PROFESIONAL GURU DI MTs DARUL HUDA MAYAK PONOROGO - Susi Fitriana; Moh. Toriqul Chaer (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
The most crucial factor for a teacher is to have four competencies, including pedagogic, personality, social, and professional. This study focused on professional competence. Professional competency ability is the teacher's competence in mastering broad and in-depth learning material that allows guiding students to meet competency standards. Teacher professional competence has the direct mastery of the scientific structure of subjects that are taken care of broadly and deeply so that it can help teachers guide students to master their knowledge or skills optimally. Based on the data collection process, an analysis of the strengths and weaknesses of the development of teacher professional competence will at MTs Darul Huda Mayak Ponorogo, and strategic competency quality offers at Madrasah MTs Darul Huda Mayak Ponorogo.